PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Fitriadi, Fitriadi; Arfah, Dwi Astuty (Restitusi : Jurnal Riset Perpajakan, 2023)
Research aims to determine the effect of tax planning, deferred tax expenses and deferred tax assets on earnings management. This research uses statistical analysis methods. The data collection method used in this research is documentation. The data collection process in this research was carried out by taking financial report data from mining companies listed on the Indonesia Stock Exchange for 2016-2019. The research results found that: Tax planning has a positive and significant effect, profit management in tax planning is carried out with the aim of maximizing profits obtained after calculating taxes. Deferred tax expenses have a positive and insignificant effect, temporary differences due to deferred tax expenses give rise to management discretion in applying principles or assumptions in financial statements. Deferred tax assets have a negative and insignificant effect, the implementation of earnings management through deferred tax assets is considered to cause losses and the financial statements are considered doubtful.